Boundary element analysis of interaction bi-material interface crack with inclusions - Peh, Yong Sheng (Nanyang Technological University, 2023)
The stress intensity factor (SIF) is an important factor for predicting the behaviour of cracks in materials. The present investigation employs a multi-region boundary element method (BEM) to simulate the interaction of a biaxially loaded bi-material, containing a circular inclusion and a crack, with an emphasis on how the inclusion affects the stress intensity factor (SIF) of the crack. In the investigation, the crack is modelled using a quadratic quarter-point crack-tip element. The bi-material under consideration is a linearly elastic isotropic material with varying material properties on both sides of a straight interface, which includes a crack. The inclusion is assumed to be circular and can be either an elastic or a rigid inclusion. The investigation results indicate that the inclusion significantly affects the stress concentration around the crack, which, in turn, affects the SIF. The stress intensity factor (SIF) is influenced by several factors, such as the inclusion and bi-material properties, as well as the relative size and position of the inclusion with respect to the crack. The boundary element method (BEM) is a reliable and precise method for studying the interaction between a bi-material containing a crack and an inclusion. The findings from this research have the potential to enhance the fracture resistance of materials and structures and evaluate the performance of structures under varying load conditions.